2009
DOI: 10.1002/prca.200800019
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative proteome investigation of the sediment portion of human urine: Implications in the biomarker discovery process

Abstract: Inherent to the biomarker discovery process is a comparative analysis of physiological states. It is therefore critical that the proteome detection protocol does not bias the analysis. With urine, the sediment portion, obtained upon thawing frozen urine, is routinely discarded prior to proteome analysis. However, our results demonstrate that such a practice inadvertently induces bias, having significant implications in the biomarker discovery process. We present the first proteome investigation of human urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Analyzing urinary sediments, which accounts for ϳ50% of the total protein content by weight (75), may offer interesting markers of prostate cancer that may be missed by solely investigating the soluble fraction. Mataija-Botelho et al identified 60 proteins in the sediment of urine, many of which were also identified in the soluble fraction, suggesting that simply discarding the sediment may alter abundance ratios of different proteins (76). EPS fluids are also an abundant source of exosomes, a subfraction that is also being targeted for discovery of prostate cancer biomarkers (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing urinary sediments, which accounts for ϳ50% of the total protein content by weight (75), may offer interesting markers of prostate cancer that may be missed by solely investigating the soluble fraction. Mataija-Botelho et al identified 60 proteins in the sediment of urine, many of which were also identified in the soluble fraction, suggesting that simply discarding the sediment may alter abundance ratios of different proteins (76). EPS fluids are also an abundant source of exosomes, a subfraction that is also being targeted for discovery of prostate cancer biomarkers (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…Doucette et al . reported the first investigation of a UP proteome identifying 60 proteins 32. By using metaproteomics approaches, we reported the identification of up to 1,887 proteins from a single UP sample40, and we showed that such protein profiles yielded information on inflammation and UTIs useful as a diagnostic test in clinical urology 34, 42.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, Johnson et al assessed cholesterol levels in urinary pellets as indicators of acute kidney injury 31. Doucette et al suggested that both SU and UP fractions should be analyzed for comprehensive biomarker discovery 32. Recently, we introduced metaproteomic approaches for the analysis of UP fractions to identify uropathogens and assess inflammatory responses for the infected patients more comprehensively 33, 34.…”
Section: Introductionmentioning
confidence: 99%
“…Unlikely, it was not possible to dissolve this precipitate using 10 mM PBS and ultrasonication. As the formation of a precipitate after thawing urine samples usually causes the missing of unique proteins [42], the method recommended by the HKUPP by the year 2010 was dismissed. Then, a number of protocols obtained also from the HKUPP and other literature were assayed [43][44][45].…”
Section: 1-preservation Of Urinementioning
confidence: 99%